2004
DOI: 10.1002/cbdv.200490102
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolism of α‐ and β‐Peptides in the Insect Heliothis virescens and in Plant Cells of Black Mexican Sweet Maize

Abstract: The tripeptide H-Val-Ala-Leu-OH and the N-Ac-tetrapeptide amide Ac-Thr-Lys-Trp-Phe-NH2, and their beta-peptidic counterparts H-beta(3)hVal-beta(3)hAla-beta(3)hLeu-OH and Ac-beta(3)hThr-(S)beta(2)hLys-beta(3)hTrp-beta(3)hPhe-NH2, respectively, have been injected into Heliothis virescens larvae and added to cell cultures of black mexican sweet maize. The body liquids of the larvae and the supernatant of the plant cell cultures were sampled 0, 2, 3, 6, 17, and/or 24 h after application and analyzed by LC/MS. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…No evidence was found to suggest that any of the peptides were cleaved by pepsin or proteinase K. Both of these enzymes prefer hydrophobic residues in the P1 and P1' cleavage positions, so this result is perhaps not wholly surprising 17 ). In any case, the knowledge about specificities of peptidases for given peptide bonds derives from studies involving pure, natural apeptides: the same preferences may not be reflected in mixed a,b-peptides, nor for that matter in pure b-peptides.…”
Section: B-peptidesmentioning
confidence: 82%
See 1 more Smart Citation
“…No evidence was found to suggest that any of the peptides were cleaved by pepsin or proteinase K. Both of these enzymes prefer hydrophobic residues in the P1 and P1' cleavage positions, so this result is perhaps not wholly surprising 17 ). In any case, the knowledge about specificities of peptidases for given peptide bonds derives from studies involving pure, natural apeptides: the same preferences may not be reflected in mixed a,b-peptides, nor for that matter in pure b-peptides.…”
Section: B-peptidesmentioning
confidence: 82%
“…± Studies performed to date have shown that b-peptides [1 ± 7] containing b-amino acids that possess natural side-chain groups are unambiguously stable to the action of several peptidases of broad substrate specificity [8 ± 14] 4 ). In addition, b-peptides are stable to metabolism by rats [16] and insects [17], although environmental microbial samples have been shown to utilize a b-tripeptide as the sole nitrogen and carbon source [18] [19].…”
mentioning
confidence: 99%
“…Once it had become clear that b-peptides were not cleaved by peptidases, we carried out in vivo tests in rats [231], in insect larvae [512], and in maize cell cultures [512]. These investigations were conducted in close collaboration with colleagues at Novartis (primarily H. Wiegand, Basel) [231] and Syngenta (R. Lind, Jealott×s Hill, UK) [378] [512].…”
Section: Louis De Brogliementioning
confidence: 99%
“…Finally, incorporation of b-amino acid residues into peptides or proteins leads to overall structural changes that confer upon them stability against proteolytic cleavage; there are numerous highly physiologically active, often toxic natural products containing one or two, sometimes more b-amino acid moieties, incorporated by the non-ribosomal peptide-synthesis (NRPS) modules [18] (for leading references, see recent review articles on b-amino acids and peptides thereof [19]). A novel type of peptide, the bpeptides, built entirely of homologated proteinogenic amino acids, have been shown to be stable in vitro and in vivo (most microorganisms [20] [21], plants [22], insects [22], rodents [23]) (see A and B). Even mixed a/b-peptides of certain sequences C are stable to proteolytic cleavage [24].…”
mentioning
confidence: 99%